The Eternal God's Response to Man's Cry in His Passing “Days” and “Years” (Ps 90) - Witczyk, Henryk (The Biblical Annals, 2020)
In Ps 90, the poet expresses his perception of man's time as marked by dynamic of passing away, fear of death, destruction, and futility. At the same time, he speaks of God's “eternity” as “You are” (v. 2). He discovers the astonishing influence of “eternity” on “time.” The prayer of the “servants” makes the distant God (full of anger and indignation – v. 11) come close to them and act in their fleeting time to evoke His “mercy,” “steadfast love,” “joy” “glorious power,” thereby making time “stable” and “permanent” (v. 17). This is anchored in God's eternity, even in God's “You are” (v. 2). In the short and transient “days” and “years” of His “servants” and their “sons,” God writes an intense experience of His eternity. The extraordinary coexistence, even the interpenetration of time and eternity in the experience of the believer (people), is perhaps the most crucial theological intuition of Ps 90.